2010
DOI: 10.1161/atvbaha.110.205674
|View full text |Cite
|
Sign up to set email alerts
|

6-Mercaptopurine Inhibits Atherosclerosis in Apolipoprotein E*3-Leiden Transgenic Mice Through Atheroprotective Actions on Monocytes and Macrophages

Abstract: Objective-6-Mercaptopurine (6-MP), the active metabolite of the immunosuppressive prodrug azathioprine, is commonly used in autoimmune diseases and transplant recipients, who are at high risk for cardiovascular disease. Here, we aimed to gain knowledge on the action of 6-MP in atherosclerosis, with a focus on monocytes and macrophages. Methods and Results-We demonstrate that 6-MP induces apoptosis of THP-1 monocytes, involving decreased expression of the intrinsic antiapoptotic factors B-cell CLL/Lymphoma-2 (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…One report states that AZA may have atheroprotective properties [34]. In this study, the authors demonstrated that in a hypercholesterolemic apoE transgenic mouse model, local delivery of 6-MP reduced atherosclerosis, mainly due to reduced activation of monocytes [34]. This effect has not yet been demonstrated by systemic application.…”
Section: Discussionmentioning
confidence: 69%
“…One report states that AZA may have atheroprotective properties [34]. In this study, the authors demonstrated that in a hypercholesterolemic apoE transgenic mouse model, local delivery of 6-MP reduced atherosclerosis, mainly due to reduced activation of monocytes [34]. This effect has not yet been demonstrated by systemic application.…”
Section: Discussionmentioning
confidence: 69%
“…Attraction and penetration of macrophages to sites of activated aorta are key to achieve continuous aortic expansion from as early as 1 day after AngII infusion ≤56 days. 10,29 The markedly reduced leukocyte influx that is observed after Aza treatment in both mouse aneurysm experiments involves reduced endothelial activation but may also partly be explained by a direct immunosuppressive effect of 6-MP on macrophages 22 and T cells. 23,25 This may also explain our reduced p-JNK found in the AAA on Aza treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Aza increases EC survival, 17 in contrast to sirolimus, which induces apoptosis, causing the thrombotic problems in sirolimus-coated coronary stents, 18 or cyclosporine A that is toxic to ECs and provokes vasculopathy. 19 We and others have previously shown that Aza maintains the contractile phenotype of smooth muscle cells 20,21 and has an anti-inflammatory effect in macrophages 22 and T cells. 23 Thus, Aza seems a good candidate drug to treat inflammation and protect the vessel wall.…”
mentioning
confidence: 94%
“…Despite the impressive progress in defining the cellular and molecular basis of inflammation and the immune response in atherosclerosis, our understanding of the impact of anti-inflammatory drugs on the development of atherosclerosis and subsequent CV events remains surprisingly incomplete. It is in this context that studies by Pols and co-workers on the impact of 6-mercaptopurine (6-MP), a metabolite of the immunosuppressive drug azathioprine (AZA), on macrophage recruitment and apoptosis in atherosclerosis are of interest7.…”
mentioning
confidence: 99%